Pendeteksian Kecurangan pada Laporan Keuangan dengan Pendekatan Fraud Triangle Model - Wibawa, I Gusti Ayu Nadya Utami Dewi; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi; Vol 33 No 10 (2023), 2023)
Pressure, opportunity and rationalization are three conditions that always occur in an act of fraud which is often called the fraud triangle, a theory developed by Cressey. This study aims to reveal aspects that support fraud using the fraud triangle model against entities listed on the Indonesia Stock Exchange, namely the property and real estate sectors in 2017-2019. This research used a population of all property and real estate companies and the number of samples used was 21 companies with observation years from 2017 to 2019, resulting in a final sample size of 63 financial reports. In this research, multiple linear regression was used as a method which was then processed first using IBM SPSS 21 software. This research obtained results that only the financial stability and ineffective monitoring variables had a positive effect on financial reporting fraud. Meanwhile, rationalization has a negative effect on fraudulent financial reporting. Keywords : Financial Stability; Ineffective Monitoring; Rationalization; Fraudulent Financial Statements.